The significance of biomarkers of inflammation in predicting the activity of lupus nephritis : Biomarkers in predicting activity of lupus nephritis - Rabrenović, Violeta; Petrovic, Milica; Rabrenovic, Milorad; Pilcevic , Dejan; Rancic, Nemanja (Journal of Medical Biochemistry, 2023)
Introduction/Aim: Lupus nephritis (LN) is one of the most serious manifestations of systemic lupus erythematosus (SLE). There are more and more studies examining the role of different markers that would facilitate diagnosis, monitoring of LN activity, occurrence of relapse as well as the right time for the introduction of maintenance therapy. Our aim was to examine the importance of determining the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), systemic immune inflammatory index (SII) and systemic inflammatory response index (SIRI) in LN, comparing their significance with other standard parameters of active desease. Material and methods: The clinical examination included a group of 89 patients, of which 66 were with LN (34 with active and 32 with LN in remission) and 23 patients in the control group - without autoimmune disease. The investigated parameters were: CRP, CBC, creatinine, albumin, GFR, C3, C4, ANA, anti ds DNA Ab, in urine: sediment analysis, proteinuria 24h and Up/cre. We determined derived markers: NLR, PLR, SIRI, SII and their correlation with other parameters of active disease. Results: Comparing the group with active LN with LN in remission and the control group, a statistically significant difference was obtained for CRP (p=0.004), and for RBW and hemoglobin, albumin, C3, ANA and anti ds DNA Ab (p<0.001) and for urinary parameters, SLEDAI/r, proteinuria 24h and Up/cre ratio. Comparing the markers: NLR, PLR, SIRI, SII between the groups, a significant difference can be observed for all selected parameters, for NLR it was the most pronounced (p<0.001). In active LN, NLR correlated with CRP, creatinine and GFR, ANA and proteinuria 24h, PLR with creatinine, ANA, proteinuria 24h, and SIRI and SII with CRP, creatinine and ANA. NLR was the parameter with the highest significance in correlations with: C3, SLEDAI/r and proteinuria (p=0.000), ANA (p=0.001), anti ds DNA Ab (p= 0.004) and Up/cre (p= 0.018). Conclusion: Our results indicate that NLR , PLR , SIRI , SII are elevated in the group of patients with active LN, and that the correlations of NLR and PLR with other activity parameters can be significant for the evaluation of active renal lesions in LN.